PENGARUH KOMUNIKASI VERBAL BERBENTUK SINDIRAN ORANG TUA TERHADAP PERUBAHAN PERILAKU PEMUDA DI PERUMAHAN TAMAN ALAMANDA KABUPATEN BEKASI - Reni Novia; Amelia Adiska Putri (Interpretasi: Communication & Public Relations, 2023)
Abstract The communication between parents and their childern can be affected to their behavior, especially to the childern in the youth age. Verbal communication between parents and their childern often do not achieve the desired goal, and one of the verbal communication used is satire. Satire is a figurative language style that does not show its true meaning. This study focuses on parental communication of satire that affects changes in children's behavior. This research uses quantitative methods, which is 54,2% respondent are women 45,8% are men, respondents are young man at age 19-24 th, in Taman Alamanda Block F. A total of 59 samples were used from the results of calculations through the method probability sampling, with technique simple random sampling. Measuring instrumet were used is Statistical Program for Social Science(SPSS) ver 25 with a reliability 0,85., such as the results of the determination test which showed that 18,8% verbal communication of parental satire has influence on children, as well as the results of hypothesis testing stating that thitung>ttabel, (3,628 > 2,002) which is Ho rejected, H1 accepted and the results of the significance test of 0.001 is smaller than the value of alpha (a) 0.05, which means that there is an influence of verbal communication in satire on behavior change over. Keyword: verbal communication, satire, youth, behavior change, parent and child communication